Rehabilitation of atrophic posterior partial edentulous maxilla with TTPHIL ALL TILT® technique: 3 year follow-up case report - Nag, Puppala Venkata Ratne; Manikandhan, Ramanathan; Sarika, Puppala; Daniel, Smitha; Vasundhara, Kaligotla Apoorva (Brazilian Dental Science, 2022)
Maxillary sinus pneumatisation pose a grave clinical challenge for implant fixed rehabilitation in posterior maxilla owing to diminished bone volume. This necessitates sinus lift and grafting which increase the duration and cost and possible surgical complications. Pterygoid implant has a greater short term osseointegration and is a proven treatment method for rehabilitation of highly resorbed posterior maxilla. To overcome the limitations of sinus grafting techniques, the current case report describes the use of flapless, tilted and pterygoid implant for restoration of partially edentulous atrophic maxilla eliminating grafting. KEYWORDS Dental Implants; Immediate Dental Implant Loading; Jaw Edentulous Partially; Surgery Computer-Assisted; Case Reports.